PENGARUH PENGGUNAAN MODEL TWO STAY TWO STRAY TERHADAP HASIL BELAJAR IPS SISWA DI SD - Khumairah, Siti; Marli, Suhardi; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to find out how much influence the use of Two Stay Two Stray model to the learning outcomes of IPS students of class III SDN 34 Pontianak City ". Research method used is experimental method with Quasi Experimental Design with Design Nonequivalent Control Group Design. Subjects of the sample were IIIE students consisting of 32 students (experiments) and 32 students (control) IIIA class. The research instrument is a matter of multiple choice test with 40 questions. Based on data analysis, the average of post test experiment class result is 79,09 and average result of post test of control class 73,25. Based on the T test with significance tarithmetic 3,169 and ttable α = 5%  equal to 1,670, which means tarithmetic (3,169)> ttabel (1,670), then Ha be accepted. Thus, it can be concluded that there is an influence of the use of Two Stay Two Stray model to the learning outcomes of Social Science students of class V SDN 25 Sungai Raya. The ES calculation is 0,56 (medium criterion). This means that the use of Two Stay Two Stray model gives a high influence on students' social learning outcomes in class III SDN 34 Pontianak City. Keywords : Influence, Two Stay Two Stray, Social Science,  Learning Outcomes